The Implementation of Digital Marketing as a Marketing Strategy for Micro, Small, and Medium Enterprises (MSMEs) - Imelda Sabrina Sibarani; Ronauli Zebua; Terintia Riahni Tampubolon; Jein Jessica Rajagukguk; Ririntri Arianti Siregar; Revalina Malau; Putri Elisa Damanik; Tasya Tatia Putri Sihite (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the implementation of digital marketing as a marketing strategy for micro, small, and medium enterprises (MSMEs) and its contribution to the development of Batak Toba and Batak Simalungun ulos products at Horas Market. The research was conducted at Misel Nadeak Ulos Store, a traditional cultural product business established in 2016. Using a qualitative research approach, data were collected through interviews, observations, and documentation involving business owners and individuals involved in digital marketing activities. The findings indicate that the adoption of digital marketing through TikTok Live and Shopee expanded market reach, increased product visibility, strengthened customer trust, and improved purchasing accessibility. Digital platforms enabled customers to access products and conduct transactions without geographical limitations. However, challenges related to human resource management and digital content consistency remained during implementation. The study concludes that digital marketing serves as an effective strategy for enhancing MSME competitiveness, business sustainability, and the promotion of traditional cultural products in the digital marketplace.